ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN VOLUME PENJUALAN PADA UMKM GRIYA MANIK DI DESA PLUMBON JOMBANG - nadya maulita; soewarno yuanita; nirawati lia (Universitas Sains dan Teknologi Komputer, 2020)
Many strategies that can be used to increase sales and attract consumers to buy products offered by manufacturers. One strategy that is widely used by companies is the marketing mix strategy. Marketing activities that focus on product self-focus, pricing, distribution policies, and means of promotion are known as the marketing mix or Marketing Mix. This study aims to evaluate the internal evaluation and indicators of the appropriate marketing mix strategy and is applied to increase the sales volume at Griya Manik-Manik Kaca Plumbon. This study uses a qualitative descriptive analysis method, by collecting data directly from the company by making observations, interviews according to the research subject. The results showed that the strategy adopted by Griya Manik-Manik Kaca Plumbon has worked well, where the four marketing strategy variables support and complement each other, and have different roles in marketing their products. We recommend that the owner of the Plumbon Griya Glass Bead UMKM should be upgraded with the marketing mix that has been applied. The strategy used by the company is good, but it would be better if the company plans to continue to improve strategies considering that many other competitors have issued similar products.